Empirical antimicrobial therapy for late-onset sepsis in a neonatal unit with high prevalence of coagulase-negative Staphylococcus - Roberta Maia de Castro Romanelli; Lêni Márcia Anchieta; Ana Carolina Bueno e Silva; Lenize Adriana de Jesus; Viviane Rosado; Wanessa Trindade Clemente (Elsevier, 2016)
Objective: The aim of this study was to compare two different empiric treatments for late-onset neonatal sepsis, vancomycin and oxacillin, in a neonatal intensive care unit with a high prevalence of coagulase-negative Staphylococcus. Methods: A cross-sectional study was conducted in an neonatal intensive care unit from 2011 to 2014. Data from the medical records of at-risk newborns were collected daily. Infections were defined according to the National Health Surveillance Agency criteria. Data analysis was performed using an internal program. Results: There was a significant reduction in the number of Staphylococcus aureus infections (p = 0.008), without endocarditis, meningitis, or lower respiratory tract infection, as well as a reduction in the frequency of deaths related to S. aureus infection. There were no significant changes in the incidence of Gram-negative bacterial or fungal infections. An increase in coagulase-negative Staphylococcus infections was observed (p = 0.022). However, there was no measured increase in related morbidity and mortality. There was a reduction in the median number of days of treatment with oxacillin from 11.5 to 6 days (p < 0.001) and an increase of one day in the median number of days of treatment with vancomycin (p = 0.046). Conclusions: Modification of the empiric treatment regimen for neonatal late-onset sepsis with use of oxacillin showed a significant reduction in S. aureus infections, as well as a reduction in the frequency of infections with major organ system involvement and mortality due to infection with this microorganism. As a result, oxacillin can be considered as an effective treatment for late-onset sepsis, making it possible to avoid broad-spectrum antibiotics. Resumo: Objetivo: Comparar dois períodos com diferentes esquemas empíricos para tratamento de sepse neonatal tardia, incluindo vancomicina ou oxacilina respectivamente, em Unidade Neonatal de referência com alta prevalência de Staphylococcus coagulase negativo. Métodos: Estudo transversal, realizado em Unidade Neonatal de referência, de 2011 a 2014. A coleta de dados foi realizada diariamente por vigilância ativa em prontuário de recém-nascidos de risco. As infecções foram notificadas conforme critérios definidos pela Agência Nacional de Vigilância Sanitária. O banco de dados e a análise foram realizados em programa interno. Resultados: Ocorreu redução significativa da notificação de infecções por Staphylococcus aureus (p = 0,008), sem notificações de endocardite, meningite e infecções de vias aéreas inferiores, além de redução na frequência de óbitos pelo micro-organismo e sem alteração significativa nas incidências de infecções por bactérias Gram negativas e fungos. Houve aumento de infecções S. coagulase negativo (p = 0,022), mas sem aumento de morbidade e mortalidade. Ocorreu redução na mediana do tempo de uso de oxacilina, de 11,5 para 6 dias (p < 0,001), com aumento de mediana de um dia de uso de vancomicina (p = 0,046). Conclusões: A modificação do esquema empírico com utilização de oxacilina revelou redução significativa das infecções por S. aureus, além da redução na frequência de infecção de foco profundo e mortalidade pelo micro-organismo. Considera-se que oxacilina pode ser utilizada como esquema de tratamento de sepse neonatal tardia, evitando-se o uso de antibióticos de largo espectro. Keywords: Sepsis, Neonate, Staphylococcus, Oxacillin, Vancomycin, Palavras-chave: Sepse, Recém-nascido, Staphylococcus, Oxacilina, Vancomicina